125I Radiotherapy combined with metronomic chemotherapy may boost the abscopal effect, leading to complete regression of liver metastasis in an SCLC patient with a 58.5-month OS: a case report - Lu, Linlin; Wang, Yu; Li, Lei; Yu, Lan; Liu, Li; Qu, Baozhen; Zhang, Xiaotao (Frontiers in Oncology, 2023)
Liver is the most common and lethal metastatic site in extensive-stage small-cell lung cancer (ES-SCLC) patients, as median survival with current standard treatment is only 9-10 months from diagnosis. Clinical observations of ES-SCLC patient sustain complete response (CR) in liver metastasis are extremely rare. Moreover, to the best of our knowledge, liver metastasis completely regression induced by the abscopal effect which mainly boosted by permanent radioactive iodine-125 seeds implantation (PRISI) combined with low-dose metronomic temozolomide (TMZ) regimen hasn’t been recorded. Here, we present a case of 54-year-old male patient who developed multiple liver metastases from ES-SCLC after multiple lines of chemotherapy. The patient was given partial PRISI (38 iodine-125 seeds in the dorsal lesion and 26 seeds in the ventral lesion, among six tumor lesions) combined TMZ metronomic chemotherapy (50mg/m2/day, Day1-21, every 28 days). The abscopal effect was been observed for one month after PRISI treatment. In about one year, all the liver masses completely disappeared without relapse. Eventually, this patient died of malnutrition caused by non-tumor intestinal obstruction with OS of 58.5 months. PRISI combined with TMZ metronomic chemotherapy might be considered as a potential therapy to trigger the abscopal effect to help more patients with liver metastases.